2019
DOI: 10.3390/genes10060453
|View full text |Cite
|
Sign up to set email alerts
|

The cGMP Pathway and Inherited Photoreceptor Degeneration: Targets, Compounds, and Biomarkers

Abstract: Photoreceptor physiology and pathophysiology is intricately linked to guanosine-3’,5’-cyclic monophosphate (cGMP)-signaling. Here, we discuss the importance of cGMP-signaling for the pathogenesis of hereditary retinal degeneration. Excessive accumulation of cGMP in photoreceptors is a common denominator in cell death caused by a variety of different gene mutations. The cGMP-dependent cell death pathway may be targeted for the treatment of inherited photoreceptor degeneration, using specifically designed and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 97 publications
2
45
0
Order By: Relevance
“…91 As such, the pathophysiology of PDE6-mediated cGMP dysregulation in the context of retinal degeneration is likely much more complex than our current understanding of cGMP homeostasis in photoreceptors. 16 Taken together with the literature, our data show that the effect of different mutations in Pde6b on whole retinal cGMP dysregulation is difficult to predict and do not correlate with cGMP-dependent photoreceptor cell death. This seeming contradiction in the results of cGMP IHC versus whole retinal cGMP is due to the inherent differences in the two assays as follows: (1) Whole retinal cGMP is quantitative but is an average measurement of all retinal cell types, while cGMP IHC is semiquantitative but is a biomarker specific to the photoreceptors.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…91 As such, the pathophysiology of PDE6-mediated cGMP dysregulation in the context of retinal degeneration is likely much more complex than our current understanding of cGMP homeostasis in photoreceptors. 16 Taken together with the literature, our data show that the effect of different mutations in Pde6b on whole retinal cGMP dysregulation is difficult to predict and do not correlate with cGMP-dependent photoreceptor cell death. This seeming contradiction in the results of cGMP IHC versus whole retinal cGMP is due to the inherent differences in the two assays as follows: (1) Whole retinal cGMP is quantitative but is an average measurement of all retinal cell types, while cGMP IHC is semiquantitative but is a biomarker specific to the photoreceptors.…”
Section: Discussionsupporting
confidence: 47%
“… 91 As such, the pathophysiology of PDE6-mediated cGMP dysregulation in the context of retinal degeneration is likely much more complex than our current understanding of cGMP homeostasis in photoreceptors. 16 Taken together with the literature, our data show that the effect of different mutations in Pde6b on whole retinal cGMP dysregulation is difficult to predict and do not correlate with cGMP-dependent photoreceptor cell death.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Rod phosphodiesterase 6 consists of a catalytic αβ complex encoded by Pde6a and Pde6b and two inhibitory γ subunits encoded by Pde6g. The control of cGMP levels by this enzyme is expected to affect both PR function and viability, as cGMP has a central role in the phototransduction cascade and PR cell metabolism [177], and elevated cGMP levels have been linked to PR cell loss [178]. Indeed, Pde6a and Pde6b mutants show depressed ERG responses at an early age and rapid PR loss with D 50 values of 11-30 days ( Figure 6, Table S1).…”
Section: Category 02: Visual Transductionmentioning
confidence: 99%
“…Cyclic guanosine-monophosphate (cGMP) is a crucial molecule for photoreceptor signal transduction and has two main cellular effectors—cyclic nucleotide gated ion channels (CNGCs) and cGMP-dependent protein kinase G (PKG) [169]. It has been reported that over-activation of PKG can be enough to cause photoreceptor cell death and that its activation levels are higher in mutant photoreceptors.…”
Section: Molecular Therapiesmentioning
confidence: 99%